The Theological Origin of “Bioethics”. Considerations about Saint Francis of Assisi. - Quesada Rodríguez, Francisco (Editorial Pontificia Universidad Javeriana, 2018)
The theologian Fritz Jahr was the creator of the word Bioethik (1927). He considered Saint Francis the inspirer of a modern movement of appreciation of the value of life, in harmony with God, the human being, and nature. The "biopsychic" dimension that explains Saint Francis' love for nature—according to Jahr—was completed by Max Scheler's "forms of sympathy." However, two philosophical criticisms were argued by two bioethicists, Peter Singer and Hans Jonas. Finally, the article presents San Francis as a model of the care of creation, according to Pope Francis.